Coordinated Ground‐Based and Space‐Borne Observations of Ionospheric Response to the Annular Solar Eclipse on 26 December 2019. Issue 11 (26th October 2020) - Aa, Ercha; Zhang, Shun‐Rong; Erickson, Philip J.; Goncharenko, Larisa P.; Coster, Anthea J.; Jonah, Olusegun F.; Lei, Jiuhou; Huang, Fuqing; Dang, Tong; Liu, Lei
Abstract: This paper studies the ionosphere's response to the annular solar eclipse on 26 December 2019, utilizing the following ground‐based and space‐borne measurements: Global Navigation Satellite System (GNSS) total electron content (TEC) data, spectral radiance data from the Sentinel‐5P satellite, in situ electron density and/or temperature measurements from DMSP and Swarm satellites, and local magnetometer data. Analysis concentrated on ionospheric effects over low‐latitude regions with respect to obscuration, local time, latitude, and altitude. The main results are as follows: (1) a local TEC reduction of ∼4–6 TECU (30–50%) was identified along the annular eclipse path, with larger depletion and longer recovery periods in the morning eclipse compared to midday. (2) The equatorial electrojet current was significantly weakened when the eclipse trajectory crossed the magnetic equator in the morning (India) sector, which contributed to large and prolonged TEC depletion therein. (3) At midday, equatorial ionization anomaly exhibited enhancements of 20–40% as well as poleward shifting of 3–4°, likely triggered by modified neutral wind and electrodynamics patterns. (4) The behavior of equatorial ionospheric electron density showed considerable altitudinal differences in the topside, exhibiting ∼30% reduction around 500 km and ∼30% enhancement with 300–500 K T e reduction around 850 km, before the arrival of maximum eclipse. This may have been caused by the enhanced eastward electric field and equatorward neutral wind, and other possible factors are also discussed. Key Points: EEJ was weakened substantially during morning eclipse, contributing to a significant TEC depletion and prolonged recovery period therein EIA crest exhibited 20–40% enhancement and 3–4° poleward shifting, likely triggered by modified neutral wind and electrodynamics patterns Topside N e showed considerable altitudinal difference, exhibiting ∼30% reduction at 500 km and ∼30% enhancements with Te reduction of 300–500 K at 850 km